2019
DOI: 10.3390/su11246952
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Risk-Taking in Sustainable Energy: University Spin-Off Firms and Market Introduction in Northwest Europe

Abstract: Universities are cradles of innovation, with many start-ups involved in sustainable energy solutions. The extent in which such solutions reach the market and the kind of risk-related factors young firms encounter, are hardly known and understood. We aim to clarify market introduction and focus on the empirics of firms’ risk-taking behavior related to strategic choices, competences, and interactions with (national) ecosystem conditions. We use a unique dataset of almost 110 university spin-off firms and a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 105 publications
0
14
0
Order By: Relevance
“…We use data on spin-off firms (a total of 106) in northwest Europe, established since 1998 [19]. The choice of countries-Denmark, Finland and Sweden-is motivated by favorable small firm and innovation conditions that allowed us to observe market introduction and longer term surviving of young technology firms, while Norway and The Netherlands are included as these have faced some less favorable conditions in (some) past years [28][29][30].…”
Section: Database Measurement and Descriptive Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use data on spin-off firms (a total of 106) in northwest Europe, established since 1998 [19]. The choice of countries-Denmark, Finland and Sweden-is motivated by favorable small firm and innovation conditions that allowed us to observe market introduction and longer term surviving of young technology firms, while Norway and The Netherlands are included as these have faced some less favorable conditions in (some) past years [28][29][30].…”
Section: Database Measurement and Descriptive Statisticsmentioning
confidence: 99%
“…The size of the sample was the outcome of a search process using universities' lists of spin-off firms, national reports on sustainable energy research/application and sector journals, like Nordic Green. We may have overlooked some spin-offs that failed before start of the data collection, but some simulation outcomes indicated no need for concern [19]. Accordingly, we may claim that the 106 firms are to a large extent representative for university spin-off firms involved in energy inventions established since 1998.…”
Section: Database Measurement and Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Renewable energy technology, such as wind and solar, especially the latter, enables more decentralized production and consumption. As some studies have shown, the market introduction of energy inventions is influenced by the energy technology involved, with solar PV (Photo Voltaic) ving more difficulty in the early years than wind energy and energy-saving [64].…”
Section: Sustainability and Interventionmentioning
confidence: 99%
“…In the context of fastening energy transition, increasingly, attention is given to the market introduction of more radical technology solutions in cities, for example, created by small spin-off firms at universities [9][10][11] (note 1 1 ). University spin-off firms can easily access new transitional technology, e.g., developed in founders' Master's or Ph.D. work.…”
Section: Introductionmentioning
confidence: 99%